خوێندنەوەیەك بۆ دۆخی سیاسی ئەوروپا پاش ڕوخانی ئیمپراتۆریەتی ڕۆمانی( ١٠٩٦-٤٧٦ز) - مستەفا, پ.د.شوان عوسمان; مستەفا, بەرهەم محەمەد (Sulaimani Journal for Humanities, 2023)
Knowing the political situation in Europe in the Middle Ages is considered as a crucial key to understand the lifestyle of European society, because the collapse of the Western Empire does not remain as an abstract political event, but rather changes the path of the historical stages in this continent. This collapse affects society in general throughout the period of the Middle Ages, along with other political events. This research focuses on the European political situation after the fall of the Western Roman Empire until the end of the eleventh century AD, and the political crises will be mentioned that afflicted Europe which they were major reasons for the backwardness of social and political life, which made researchers to call this period of the dark ages. This study aims to provide a general knowledge of the political situation in Europe during that period, and to clarify its impacts on social life, and it is tried to obtain a convincing answer to those questions that state the reasons for the backwardness of European society and call it the Dark Ages, however, factors will be explained that made clerics become the owner of their own power as the result of their interference in the affairs of secular power, and for conducting this research, descriptive historical and analytical approach is adopted. One of the most important findings that we reached is that, with the collapse of the Western Roman Empire and the loss of central authority, it became in a political vacuum for a long time and became a field of Germanic tribal conflicts and tendencies, and Europe became an unsafe country, and this directly negatively affected society and in all respects. Nevertheless, religious authority appeared on a large scale by taking advantage of the resulting opportunity and made Christianity the dominant religion in the Middle Ages in Europe This is why the local princes and dukes who played their role in the political tasks that replaced the central authority as a result of the weakness of the authority of the Carolingian emperors and kings, but rather they who protected their country from the dangers of the second Germanic tribal attacks.